The Effect of Perceived Product Quality and Perceived Price on Repurchase Intention Mediated by Customer Satisfaction: A Study of Gatsby Perfume Users in Greater Bandung - Dimas Eka Chandra; Leni Evangalista Marliani (International Journal of Management Science and Information Technology, 2026)
The intensifying competition in Indonesia's men's fragrance industry has increasingly pressured the competitive position of well-established brands, including Gatsby, which recorded a consistent decline in its Top Brand Index throughout 2023–2025 amid the growth of competitors such as Evangeline and Morris. This study aims to examine the influence of Perceived Product Quality and Perceived Price on Repurchase Intention, both directly and through the mediation of Customer Satisfaction, among Gatsby perfume users in the Greater Bandung area. A quantitative approach employing descriptive and associative methods was used in this study. Data were collected through a structured questionnaire distributed to 100 respondents selected using purposive sampling. The research instrument was found to be valid and reliable, and the data satisfied all classical assumptions required for regression analysis. Data were analyzed using Multiple Linear Regression and the Sobel test with the assistance of IBM SPSS Statistics. The results show that Perceived Product Quality and Perceived Price each have a positive and significant effect on both Customer Satisfaction and Repurchase Intention, Customer Satisfaction also has a positive and significant effect on Repurchase Intention, and Customer Satisfaction is shown to significantly mediate the influence of Perceived Product Quality and Perceived Price on Repurchase Intention. These findings indicate that consumers are more inclined to repurchase Gatsby perfume when the product quality is perceived as good, the price is considered fair, and their satisfaction is formed through expectation confirmation. This study offers practical insight for PT Mandom Indonesia in formulating strategies to improve product quality, pricing, and customer-satisfaction reinforcement in order to strengthen consumers repurchase intention.